Evaluation of survival of Staphylococcus aureus and Clostridium botulinum in charqui meats - Lara, JAF; Senigalia, SWB; Oliveira, TCRM; Dutra, Iveraldo dos Santos [UNESP]; Pinto, Marcos Franke [UNESP]; Shimokomaki, M. (Elsevier B.V., 2003)
Charqui meats were prepared in laboratory conditions in order to carry out experiments to observe the possibility of development of enterotoxigenic Staphylococcus aureus and Clostridium bottilinum proteolytic type B spores and their toxins. Results demonstrated that the harsh processing conditions, high salt concentration, relative high temperature, a, values, inhibited the growth of both bacteria. Under our experimental conditions, S. aureus would survive throughout the sequence of salting steps i.e. brine followed by rock salting and the sunshine drying step. However, at final a(w) value of 0.70-0.75 would create conditions to inhibit its development. The other experiment revealed that C. botulinum spores germination also was impaired because of these low a(w) values. Under these conditions, charqui meats revealed to be safe products in relation to toxins from both enterotoxigenic S. aureus and C. botulinum. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: intermediate moisture meat product; hurdle technology; Clostridium botulinum; Staphylococcus aureus